Effects of dietary allspice, Pimenta dioica powder on physiological responses of Oreochromis mossambicus under low pH stress - Gultepe, Nejdet; Ergün, Sebahatti̇n; Kesbic, Osman Sabri; Acar, Umit; Yilmaz, Sevdan (Springer Science and Business Media LLC, 2015)
This study investigated the effects of the supplementation with allspice (0, 5, 10, 15, or 20 g kg(-1)) on the haemato-immunological and biochemical variables in tilapia, Oreochromis mossambicus under acidic stress condition. In a 60-day feeding trial, 15 aquariums (80-L) were stocked with 18 fish (20.05 ± 0.10 g) each. Then, acidic stress was achieved by exposing the sampled fish to acidic water (pH 5.5) for 3 days. Allspice supplementation influenced the haematological indices, serum glucose, protein, globulin and innate immune parameters such as respiratory burst activity, lysozyme, and myeloperoxidase activities. In general, at acidic pH decreased circulating red blood cell numbers (RBC), increased mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) and the innate immune parameters were observed. On the other hand, the inclusion of allspice prevented an increase in blood glucose MCV and MCH, decreases in albumin, RBC, lysozyme activity and respiratory burst avtivity. In conclusion, this study demonstrated that allspice supplementation at 10 g kg(-1) for 60 days, has adequate beneficial effects on improvement of haemato-immunological and biochemical status of O. mossambicus after stressful management.
Keywords: Supplementation; Research; Plant; Hematology; Biochemistry; Tilapia; 2. Zero hunger; 10. No inequality; 3. Good health